Upregulation of CD20 positive B-cells and B-cell aggregates in the tumor infiltration zone is associated with better survival of patients with pancreatic ductal adenocarcinoma - Brunner, Maximilian; Maier, Katharina; Rümmele, Petra; Jacobsen, Anne; Merkel, Susanne; Benard, Alan; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Weber, Georg (International Journal of Molecular Sciences, 2020)
Patients with pancreatic ductal adenocarcinoma (PDAC) normally have a poor long-term prognosis. However, some rare cases of long-term survivors have been reported. The tumor microenvironment, consisting of cellular and stromal components, possibly plays an important role and might influence prognosis. In this context, the role of tumor-infiltrating B-cells and its impact on the survival in patients with PDAC remains controversial. We therefore aimed to assess the prognostic value of CD20-positive B-cells and CD20-positive B-cell aggregates as well as CD138, IgM, Pax5, and Ki67 on the survival of patients with PDAC using immunohistochemistry of FFPE pancreatectomy tissue sections from patients that underwent primary surgery for pT3-and R0-pancreatic adenocarcinoma between 1995 and 2016. Patients with PDAC were matched and grouped in 16 long-term-survivors (LTS, median overall survival (OS): 96 months [range: 61–177 months]) and 16 short-term-survivors (STS, median OS: 16 months [range: 7–32 months]). CD20-positive B-cells and B-cell aggregates in the tumor infiltration zone were significantly upregulated in the LTS-group compared to the STS-group (p = 0.0499 respectively p = 0.0432). Regarding the entire patient cohort (n = 32) CD20 positive B-cell aggregates in the tumor infiltration zone were an independent prognostic marker for overall survival in multivariate analysis (HR 9.2, CI 1.6–51.4, p = 0.012). These results underline the importance of tumor-associated B-cells for prognosis of patients with PDAC. The detailed role of B cells in the pathomechanism of PDAC should be further investigated for predicting outcome, identifying appropriate treatment regimens, and developing novel therapeutic options.
CRIS-Team Scopus Importer:2020-03-17
Keywords: B-cell aggregates; B-cells; CD20; Pancreatic ductal adenocarcinoma; Survival